Evaluating the Impact of Green Supply Chain Management Processes on New Products in Saipa Automotive Company - Einizadeh, Ali; Kasraee, Ahmad Reza; Mirabi , Vahidreza (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: The development of new products is a strategic activity for many automotive companies to gain a competitive advantage. This requires the examination of variables that affect the performance of new product development. This article evaluates the impact of green supply chain management processes on new products at Saipa Automotive Company.Methodology: The research method is descriptive and survey-based. The research population includes managers from various departments at Saipa Automotive Company. Data were collected using a field method and a questionnaire with a convenience sampling technique. For data analysis, the Structural Equation Modeling approach with Partial Least Squares and the PLS software were used.Findings: Findings indicate that internal processes positively impact green practices. Furthermore, the impact of variables such as green supply chain actions, environmental characteristics, and supply chain agility on supply chain value creation was positive. Additionally, the results showed that supply chain value creation significantly impacted the development of new (green) products.Conclusion: Therefore, it is recommended that automotive industry companies use customer ideas in developing green products and seek their opinions on products and their modifications to enhance supply chain value creation and product quality.